sVEGFR1 Is Enriched in Hepatic Vein Blood—Evidence for a Provisional Hepatic Factor Candidate? - Spearman, Andrew D.; Gupta, Ankan; Pan, Amy Y.; Gudausky, Todd M.; Foerster, Susan R.; Konduri, G. Ganesh; Ramchandran, Ramani (Frontiers in Pediatrics, 2021)
Background Pulmonary arteriovenous malformations (PAVMs) are common sequalae of palliated univentricular congenital heart disease, yet their pathogenesis remain poorly defined. In this preliminary study, we used paired patient blood samples to identify potential hepatic factor candidates enriched in hepatic vein blood. Methods Paired venous blood samples were collected from the hepatic vein (HV) and superior vena cava (SVC) from children 0-10 years with univentricular and biventricular congenital heart disease (n=40). We used three independent protein analyses to identify proteomic differences between HV and SVC blood. Subsequently, we investigated the relevance of our quantified protein differences with human lung microvascular endothelial assays. Results Two independent protein arrays (semi-quantitative immunoblot and quantitative array) identified that soluble vascular endothelial growth factor receptor 1 (sVEGFR1) is significantly elevated in HV serum compared to SVC serum. Using ELISA, we confirmed the previous findings that sVEGFR1 is enriched in HV serum (n=24, p<0.0001). Finally, we studied the quantified HV and SVC serum levels of sVEGFR1 in vitro. HV levels of sVEGFR1 decreased tip cell selection (p=0.0482) and tube formation (fewer tubes [p=0.0246], shorter tube length [p=0.0300]) in vitro compared to SVC levels of sVEGFR1. Conclusions Based on a small heterogenous cohort, sVEGFR1 is elevated in HV serum compared to paired SVC samples, and the mean sVEGFR1 concentrations in these two systemic veins cause pulmonary endothelial phenotypic differences in vitro. Further research is needed to determine whether sVEGFR1 has a direct role in pulmonary microvascular remodeling and PAVMs in patients with palliated univentricular congenital heart disease.